Enantioselective Separation and Determination of Formoterol in Bulk Drugs and Formulations by High Performance Liquid Chromatography - Padmanabha Reddy, Y.; Mohana Vamsi, N.; Shrivas, Manish; Sunil Kumar, M.V. (Asian Journal of Chemistry, 2011)
A simple and rapid liquid chromatographic methods for enantioselective separation and determination of -(±)- enantiomers of formoterol (FMT) in bulk drugs and formulations using UV and polarimetric detectors connected in series was developed. The enantiomers were tested on numerous commercial HPLC columns. For formoterol the most convenient separation was determined on amylose chiralpak AD-H column. The mobile phase compositions were systematically studied to obtain the optimal chromatographic methods. Validation of methods in selected conditions shows that the chosen methods are selective and precise with linear response of detector for both pairs of enantiomers.